Analysis of the Relationships between Financial Development and Economic Growth through Romer's Expanding Variety of Products Model: The Case of Turkey - YILMAZ, Oguzhan (International Journal of Economics and Financial Issues, 2016)
In this article the relation between financial development and growth is examined with the help of the Romer model. In the model growth of the economy is sustained by consistent innovations and openings of new sectors that require large scale and long-term committed capital. We propose that only a well-developed financial system can provide the necessary efficient flow of capital in the economy and enable more diversification and stimulation of investment in more productive but riskier areas. Defining different monetary, loan and security variables as indicators of financial development, long-term equilibrium relation with national income was studied through time series analysis with data belonging to the Turkish Economy. The econometric results support the hypothesis about existence of a co-integrating relation between financial development and growth. Keywords: Financial Development, Romer Growth Model, Innovation, Co-integration JEL Classifications: C22, F4, O16, O31, 052